2022
DOI: 10.1371/journal.pone.0274635
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy of infertility in Ghana: Why do infertile patients discontinue their fertility treatment?

Abstract: Background Globally, millions of people of reproductive age experience infertility. With that notwithstanding, most infertile patients undergoing pharmacotherapy withdraw from treatment before achieving the desired outcome. The reasons for their withdrawal, particularly in sub-Saharan Africa, have not been well examined, hence the need for this study. Objectives The aim of the study was to examine why infertile patients discontinue pharmacotherapy prior to achieving conception. Methods The study employed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In spite of these findings, in many areas of the world, both men and women are hesitant to blame infertility to the male partner, a feature considered to contribute to the low number of males seeking fertility therapy. 12,21 Surprisingly, financial problems were not given as a reason to stop treatment. When we did our study in Belgium, most of the cost of the medicine to stimulate the ovaries was covered, but the lab costs for IVF/ICSI were not covered and patients had to pay a lot per cycle (about 1,500-2,000 EUR).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of these findings, in many areas of the world, both men and women are hesitant to blame infertility to the male partner, a feature considered to contribute to the low number of males seeking fertility therapy. 12,21 Surprisingly, financial problems were not given as a reason to stop treatment. When we did our study in Belgium, most of the cost of the medicine to stimulate the ovaries was covered, but the lab costs for IVF/ICSI were not covered and patients had to pay a lot per cycle (about 1,500-2,000 EUR).…”
Section: Discussionmentioning
confidence: 99%
“…Arhin, et al (2022) 12 showed the most common reasons for stopping infertility treatment were a lack of support from male partners, looking for alternative treatments, unfulfilled outcome expectations, unsatisfactory medical services, physical distance, social stigma, and moving away from the original treatment center. They asked patients and healthcare providers why infertile people stop fertility treatment before conceiving.…”
Section: Couplementioning
confidence: 99%
“…For example, our recent report revealed that prolonged pharmacotherapy of infertility without the desired outcome might lead to apathy, increased financial burden, psychological distress, and subsequent withdrawal from treatment. 7 Therefore, increasing the expected outcome of pharmacotherapy for infertility by employing evidence-based treatment protocols may significantly reduce treatment discontinuation and its associated psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the high preference for pharmacotherapy in managing infertility in the subregion, extensive and meticulous studies to ascertain the outcome of these treatments cannot be overemphasized. 7 Nonetheless, no study properly and convincingly evaluates the outcome of pharmacotherapy for infertility among women seeking fertility treatment in the subregion because data on conception rates remain scanty. Among the few related studies conducted in Southeast Nigeria focused only on conventional therapy, although other modes of treatment such as nutritional and herbal therapies form an integral treatment modality in sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Fertility treatments can be financially burdensome, physically demanding, and emotionally draining on couples [ 12 ]. Fertility treatment in Ghana can be financially burdensome as it is not covered under the National Health Insurance Scheme (NHIS) and couples have to fully pay for all services and treatment [ 13 ]. By unravelling the psychosocial contexts of infertility, this paper aims to uncover the nuances, offering insights that may guide clinicians, counsellors, and support groups in providing more comprehensive care.…”
Section: Introductionmentioning
confidence: 99%